Dietary protein supplementation and its consequences for intake, digestion, and physical activity of a carnivorous marsupial, Sminthopsis crassicaudata. Issue 7 (5th March 2018) - Yuan, Lihong; Wilder, Shawn; Raubenheimer, David; Simpson, Stephen J.; Shaw, Michelle; McAllan, Bronwyn M.
Abstract: Diet regulation behavior can mediate the consequences of imbalanced diets for animal well‐being, particularly for captive species that have little dietary choice. Dasyurids (carnivorous marsupials) are of conservation concern in Australia, and many species are in captive breeding programmes. However, their nutrient targets and dietary regulation behaviors are poorly understood, a limitation that may decrease the breeding success and well‐being of captive animals. We tested how dietary protein content influenced the intake and utilization of nutrients, physical activity, and body mass of fat‐tailed dunnarts Sminthopsis crassicaudata . Twelve adult dunnarts from six sibling pairs (one female and one male per pair) were provided ad libitum access to three diets in a repeated measures design: cat food, cat food supplemented with raw lean beef (1:1), and cat food supplemented with cooked lean beef (1:1). Food intake, activity level, and fecal output were measured daily. Dunnarts significantly decreased food intake, increased protein digestion, and physical activity, but body mass was unchanged when on the high‐protein diet compared to the normal cat food diet. These observations suggest a capacity of dunnarts to maintain constant body mass using a dynamic balance of feeding, digestion, and activity. We also found a significant effect of family, with differences between families as large as the difference between the diet treatments, suggesting a genetic component to diet selection. The nutrient regulation responses of dunnarts to high‐protein diets and the strong family effects provide important messages for the management of populations of small carnivores, including the aspects of dietary manipulation and conservation of genetic diversity. Abstract : When challenged with diets with different protein components, the small marsupial carnivore, Sminthopsis crassicaudata, moderated food intake and increased activity when on a high‐protein diet, but body mass did not change. Surprisingly, there was a large effect of their genetic background on activity and food consumption; this effect was as large as the effect from the diets and sends a cautionary message about assumptions concerning food consumption in captive and wild animals.